Two Unusual Cases of Adult Onset Congenital Bronchoesophageal Fistulas Treated With Fistula Division - BATIREL, HASAN FEVZİ (ELSEVIER SCIENCE INC, 2014)
Adult onset congenital bronchoesophageal fistula is a very rare entity. We report 2 cases of adult onset type II congenital bronchoesophageal fistula between the distal thoracic esophagus and the lower lobe superior segmental bronchi surgically treated through a right and left thoracotomy, respectively. In both cases the fistula was transected and sutured with no parenchyma resection. Both patients had an uneventful recovery. Resection of the underlying parenchyma during surgery for bronchoesophageal fistula is not always necessary as the lung can heal in time after performing just fistulectomy. (C) 2014 by The Society of Thoracic Surgeons